Bioentrepreneurship Learning Implementation: Analysis of Students' Critical Thinking Skills - Nur Hayati; Lina Arifah Fitriyah; Andri Wahyu Wijayadi; Oktaffi Arinna Manasikana; Noer Af’idah (Universitas Tidar, 2024)
Critical thinking skills are needed by students to solve problems in real life, such as environmental problems related to waste in the environment around students. The purpose of this study is to improve students' critical thinking skills through bioentrepreneurship learning. This research is Classroom Action Research (CAR), consisting of two cycles, where each cycle includes planning, implementing, observing, and reflecting stages. The subjects involved in this research are students of study program X of Jombang X University class of 2020. Data collection techniques are carried out through observation and tests. This study used instruments in the form of observation sheets and critical thinking skills assessments in the form of description questions. The data is analyzed in a qualitative, descriptive way through the calculation of the average score obtained. The conclusion of the research results is that there is an increase in the average critical thinking skills of students through the implementation of bioentrepreneurship learning with project activities from cycle I to cycle II. In cycle I, students' average critical thinking skills were 2.89 with the criteria of